The history of the subaltern groups: Rome and the Middle Ages in Italy - Bellina, Camilla; Bianchi, Erica; Boothman, Derek; D'Alessandro, Monica; Ferraresi, Adriano; Foschi, Maria Lucia; Guerrieri, Manuel; Locatelli, Marco; Malaguti, Luna; Palmeri, Frederica; Romolo, Angela; Tassinari , Caterina (International Gramsci Journal, 2023)
Given the international interest, debate and controversy on questions of the subaltern classes and of relationships of hegemony, it has been thought useful to present here a number of sections (conventionally called paragraphs) from the Prison Notebooks that are as yet awaiting publication in an English translation. They will of course come out in Joseph Buttigieg’s ongoing project of the translation in their entirety of the Gerratana edition of the Notebooks, and publication of some of Gramsci’s first drafts of the pieces here included are imminent. In other cases, however, the first drafts by Gramsci, especially the paragraphs discussing Ettore Ciccotti’s articles, have actually been published in the second volume of the Buttigieg edition,1 not to mention of course editions in languages other than English. Apart from Gramsci’s general discussion of the emergence of the subaltern classes and their struggle for recognition and even some sort of hegemony, what readers may find of further interest is the way in which he reworks and elaborates his arguments either in detail or at the level of what often appear relatively minor specifications.